A nonlinear numerical model for comparative study of acoustic-gravity wave propagation in planetary atmospheres: application to Earth and Mars - Srivastava, Sarthak (2023)
A two-dimensional nonlinear numerical model has been developed to study atmospheric coupling due to vertically propagating acoustic gravity waves (AGWs) on different planets. The model is able to simulate both acoustic and gravity waves due to inclusion of compressibility. The model also considers dissipative effects due to viscosity, conduction, and radiative damping. The hyperbolic inviscid advection equations are solved using the Lax-Wendroff method. The parabolic diffusion terms are solved implicitly using a linear algebra-based Direct method. The model is validated by comparing numerical solutions against analytical results for linear propagation, critical level absorption, and mountain wave generation over an isolated hill. Acoustic wave generation in Martian atmosphere due to a pressure pulse is also demonstrated. A case study of tsunami-generated AGWs is presented for the 2004 Sumatra earthquake whereby the model is forced through tsunamigenic sea-surface displacement. The properties of simulated AGWs closely match those derived from ionospheric sounding observations reported in literature. Another application for Martian ice cloud formation is discussed where gravity waves from topographic sources are shown to create cold pockets with temperatures below the CO2 condensation threshold. The simulated cold pockets coincide with the cloud echo observations from the Mars Orbiting Laser Altimeter aboard Mars Global Survey spacecraft.